ASCERTAINMENT OF ADMISSIBLE SYSTEMATIC OVERLOADS IN THE DISTRIBUTIVE OIL-TRANSFORMERS - V. A. Anishchenko; V. V. Ivanov (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The capacity of power-distributive oil-transformers is selected on the basis of their operational mode cost-effectiveness and power-supply reliability of the electrical recipients on condition that the transformers duty should not lead to reduction of their normal life-in-service. Unconscionable and protracted overloads intrinsically decrease reliability and respectively service life of the transformers owing to increased wear of the winding insulation because of the excessive heat. The unaccounted previous loading history and possible changes of the risen overload in the course of its further development can lead to poor accuracy in the admissible overload time estimation. Therefore, that may lead to intolerable excessive heat in the winding insulation or underutilization of the potential overload capacity of the transformers. Which limits the potentiality of complete demand satisfaction of the electrical consumers. This is exactly why the acting GOST 14209–97 strongly recommends the consumers to make their own calculations of the load-carrying capacity based on the real load curves.The authors present a method for ascertainment of the admissible duration of the systematic non-emergency overload of a distributive oil-transformer. The ascertainment method accounts for the overload repetition-factor alteration on the time-interval of its occurrence and respectively the variation in the transformer thermal state. The employment of this method will allow improving accuracy in ascertainment of the admissible duration of the systematic non-emergency overloads and eventually the reliability of the transformer operation and the power-supply system in its entirety. The method realization is intended by means of the transformer-load monitoring as one of the tasks of the electric-energy automated control and accounting system.